The Battle for the Roads of Britain - Taylor, David. author. aut Link
XII, 238 p.
Keywords: Policing in Britain was changed fundamentally by the rapid emergence of the automobile at the beginning of the twentieth century. This book seeks to examine how the police reacted to this challenge and moved to segregate the motorist from the pedestrian in an attempt to eliminate the 'road holocaust' that ensued.